Unique rheological behavior of detonation nanodiamond hydrosols: The nature of sol-gel transition. (May 2020) - Kuznetsov, Nikita M.; Belousov, Sergey I.; Bakirov, Artem V.; Chvalun, Sergei N.; Kamyshinsky, Roman A.; Mikhutkin, Alexey A.; Vasiliev, Alexander L.; Tolstoy, Peter M.; Mazur, Anton S.; Eidelman, Eugeny D.; Yudina, Elena B.; Vul, Alexander Ya
Abstract: The paper describes the data on unusual rheological properties of detonation nanodiamonds (DND) hydrosols and presents the fractal model explaining such behavior. The hydrosols of DND with particles size of 4–5 nm and concentration range of 1.1–7.3 wt% with negative ( ζ  < 0) and positive ( ζ  > 0) electrokinetic potentials have been studied by rotational viscometry, small-angle X-ray scattering, nuclear magnetic resonance and Cryo Electron Tomography. Remarkable hysteresis of viscosity and thixotropic effect demonstrate the sol-gel transition at very low concentrations of the DND: 4–5 wt% for ζ  > 0 and 5–6 wt% for ζ  < 0. The transition is accompanied by increase of loss (viscosity) modulus by two orders of magnitude and the storage (elasticity) modulus started to be detected also. The experimental results have been explained in the frame of percolation theory based on the network formation due to faceted DND particles interactions. Graphical abstract: Image 1